+0  
 
+3
546
3
avatar+1832 

 

 

 

 

 Aug 16, 2014

Best Answer 

 #3
avatar+121078 
+13

Yes, xvxvxv, e is correct for the second question.

As to your hypothesis...let's see if this it is true that cos(n*pi + x) = cos(x)

Using a trig identity, we have

cos(n*pi + x) =

cos(n*pi)cos(x) - sin(n*pi)sinx  =

cos(n*pi)cos(x)

Notice that this equals cos(x) only when n = 0, 2, 4, 6......

 

 Aug 16, 2014
 #1
avatar+32822 
+13

Two answers!

Alan Aug 16, 2014
 #2
avatar+1832 
+3

nice alan .. so question 2 the answer is e ! right ? 

 

and I want to ask ... from your amswer in question 6 I Concluded this law                                                                   cos(npi + x ) = cos(x)    ...  n mean any Integer number ( 0 , 1 , 2 , 3 ....... ) 

 Aug 16, 2014
 #3
avatar+121078 
+13
Best Answer

Yes, xvxvxv, e is correct for the second question.

As to your hypothesis...let's see if this it is true that cos(n*pi + x) = cos(x)

Using a trig identity, we have

cos(n*pi + x) =

cos(n*pi)cos(x) - sin(n*pi)sinx  =

cos(n*pi)cos(x)

Notice that this equals cos(x) only when n = 0, 2, 4, 6......

 

CPhill Aug 16, 2014

23 Online Users

avatar
avatar